2017
DOI: 10.4253/wjge.v9.i8.346
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz endoscopic imaging for colorectal cancer detection: Current status and future perspectives

Abstract: Terahertz (THz) imaging is progressing as a robust platform for myriad applications in the field of security, health, and material science. The THz regime, which comprises wavelengths spanning from microns to millimeters, is non-ionizing and has very low photon energy: Making it inherently safe for biological imaging. Colorectal cancer is one of the most common causes of death in the world, while the conventional screening and standard of care yet relies exclusively on the physician’s experience. Researchers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…59 At present, the hypothesis have been performed by four procedure in sequence, showing the sensitive screening for colorectal cancer. 60…”
Section: Terahertz Imaging Of Tissuementioning
confidence: 99%
“…59 At present, the hypothesis have been performed by four procedure in sequence, showing the sensitive screening for colorectal cancer. 60…”
Section: Terahertz Imaging Of Tissuementioning
confidence: 99%
“…Additionally, different types of THz endoscopes were created, which made it possible to discriminate between normal and cancer tissues in vivo [12,13]. It is expected that further development of THz technologies will make it possible to create new effective and commercially inexpensive devices for the diagnostics of digestive systems, based on the THz methods [14]. Thus, all of these studies showed a large potential of THz methods in gastric cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, as THz radiation is characterized by the strong water absorption [12], this frequency range can be used as a sensitive and precise non-invasive hydration probe, in particular, to monitor biotissue dehydration [13,14]. The development of a new tool for highly accurate non-invasive assessment the of water content within the biological tissues would help enormously in such areas as cancer diagnosis [15][16][17][18][19], food and other products quality control [8,20] or plants' stress responses monitoring [21][22][23].…”
Section: Introductionmentioning
confidence: 99%